Financial Performance Assessment of PT Telekomunikasi Indonesia TBK in Comparison with other Telecommunication Companies Locally and Globally 2008-2012 - Elan, Joviano Rinaldi; Soekarno, Subiaktp (Journal of Business and Management, 2013)
Telecommunications industry has been growing fast in the past decade along with the globalization era. It has drawn attention from investors all over the world to invest money in telecom companies. Each country races to develop their telecommunications to support infrastructure. Indonesia is one of the growing countries that faces globalization. Indonesia has been trying to build a good fundamental by developing its infrastructural sectors. One of the subsectors included in infrastructure is telecommunications. PT Telekomunikasi Indonesia Tbk (Telkom) is one of the telecommunications services companies in Indonesia. The company was established in 1856 as a state-owned enterprise and has been growing rapidly since then. Telkom has the largest market share than any other telecom companies in Indonesia. Telkom’s growing demand in top quality service calls for an excellent performance of the company that includes financial, operation, and management performance. From the brief explanation above, many questions arise regarding to its performance. How is the performance of Telkom compared to other telecom companies in Indonesia? How is the performance of Telkom among global telecom companies? What could be recommended in order to improve Telkom’s performance in the future? The sample of this research is public listed telecommunications companies in Indonesia Stock Exchange and top public telecommunication companies within Asia Pacific for the period of 2008-2012. The ratio analysis is conducted to compare Telkom’s performance with other companies. Additionally, BUMN rating, Moody’s rating, and the Economic Value Added (EVA®) methodology is used to rank the companies. From the analysis that has been conducted, it shows that the performance of the company is the best among the other telecom companies in Indonesia. However, Telkom’s performance is still below global telecom companies. Hence, Telkom require improvements in order to compete in the global market and expand its business globally. Suggested aspects to be improved by Telkom are costumer loyalty and segmentation, growth, cost reduction, innovation and diversification, complexity reduction, mergers and acquisitions, and pricing policies. From the actions above, Telkom will certainly be able to sustain good performance and compete better globally. Keywords: Telkom, financial, performance, analysis, BUMN, Moody’s, EVA----------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.